Peran Kepuasan Kerja dalam Memediasi Pengaruh Stres Kerja terhadap Turnover Intention pada Karyawan BPR Bali Dananiaga - Kadek Meira Salsabila Maharani; Ida Bagus Ketut Surya (Journal Of Business, Finance, and Economics (JBFE), 2024)
The aim of this study is to analyze the role of job satisfaction in mediating the effect of job stress on turnover intention. Turnover intention is an employee's intention or desire to move from one workplace to another but is not yet at the reality stage. This study was conducted at BPR Bali Dananiaga. This study used 52 samples using the saturation sampling method. The data collection methods used were interviews and questionnaires. The data collection was then analyzed using descriptive analysis, path analysis techniques, classical assumption test and the sobel test. The study results show that job stress has a positive and significant effect on turnover intention. Job stress has a negative and significant effect on job satisfaction. Job satisfaction has a negative and significant effect on turnover intention. Job satisfaction mediates the effect of job stress on turnover intention. It is hoped that the implications of this research can be a consideration for companies to reduce turnover intention by considering job stress and job satisfaction.